EDUCATIONAL GAMES: HOW TO STIMULATE CREATIVE ABILITIES IN STUDENT DEVELOPMENT - Karimova Nilufar Raimzhanovna (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2026)
The article presents the definition of the concept of didactic resources, the result of a study of the cognitive development of children preparatory to school and the results of a survey of parents.